Barrier and facilitator on breastfeeding education and promotion: A literature review - Lina Handayani; Maya Kusuma Dewi; Lafi Munira (Intelektual Pustaka Media Utama, 2020)
Breast milk contains many nutrients according to the needs of the baby for growth and development. Breast milk is very important for the health and well-being of infants. The world health organization recommends exclusive breastfeeding mothers for six months starting from the baby's first life and continuing until the age of two. Breastfeeding can provide economic benefits for the family and community. This study aimed to explore the barrier and facilitator on breastfeeding promotion and education. This study was literature study. This study finding that support from the baby's father is needed as a strong decision exclusively breastfeeding mothers. Pediatricians and midwives have an important role to support in providing exclusive breastfeeding from mothers and infants. Mothers who work full time find it very difficult to care for their babies exclusively. The workplace can be a barrier for mothers to care for and provide exclusive breastfeeding. Breastfeeding competency-based training is needed as a more optimal promotion of exclusive breastfeeding. Promotion of breastfeeding can increase the duration and exclusivity of breastfeeding. Knowledge promotes breastfeeding can increase the chances of successful breastfeeding and improve baby's health. An important role in the successful promotion of breastfeeding is the quality of knowledge and support for exclusive breastfeeding.